Quality Parameters of Juice Obtained from Hydroponically Grown Tomato Processed with High Hydrostatic Pressure or Heat Pasteurization - Maja Jeż; Wioletta Błaszczak; Kamila Penkacik; Ryszard Amarowicz (International Journal of Food Science)
The effect of processing such as high hydrostatic pressure (HHP) (400-600 MPa/15 min) or low pasteurization temperature (LPT) (74°C/2 min) or high pasteurization temperature (HPT) (90°C/1 min) on selected quality parameters of juice obtained from hydroponically cultivated beef tomatoes was investigated. The total polyphenols content (TPC), total phenolic index (TPI), Trolox equivalent antioxidant capacity (ABTS) and ferric reducing antioxidant power (FRAP) were analysed in the fresh and processed juices stored for 0, 7 and 14 days. What is more, colour parameters (L∗,a∗,b∗,∆E), the activity of polyphenol oxidase (PPO) and peroxidase (POD) and microbial stability were also analyzed following the juices storage. Among all the tested samples, the juice exposed to 600 MPa for 15 min showed superior quality. Samples treated with 600 MPa for 15 min and stored for 0, 7 and 14 days had high TPC, TPI, ABTS, FRAP and a∗ values. As demonstrated, these tested samples at the end of the storage period retained 90% and 95% of their polyphenol content and antioxidant capacity, respectively. As in the case of pasteurization, juice processing at 600 MPa for 15 min clearly reduced the activity of food-spoiling enzymes (PPO, POD) as well as the microbial count. The obtained results showed that TPC was significantly and positively correlated with TPI, ABTS and FRAP parameters.